2022
DOI: 10.3390/horticulturae8080732
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Eggplant DIR Gene Family in Response to Biotic and Abiotic Stresses

Abstract: Dirigent proteins (DIR) play important roles in the biosynthesis of lignins and lignans, defensive responses, secondary metabolism, and disease resistance in plants. The DIR gene family has been identified and studied in many plants. However, the identification of DIR gene family in eggplant has not been conducted yet. Therefore, in this study, based on the available genome information of eggplant, the DIR family genes in eggplant were identified with bioinformatics methods. The expression pattern analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…8 ). Specifically, these sequences were obtained from tobacco, potato, eggplant [ 16 ], cotton [ 5 ] and Arabidopsis [ 3 ] (Additional file 5: Table S5 ). The phylogenetic reconstruction delineated the evolutionary clustering of the DIR gene family into three discernible subfamilies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…8 ). Specifically, these sequences were obtained from tobacco, potato, eggplant [ 16 ], cotton [ 5 ] and Arabidopsis [ 3 ] (Additional file 5: Table S5 ). The phylogenetic reconstruction delineated the evolutionary clustering of the DIR gene family into three discernible subfamilies.…”
Section: Resultsmentioning
confidence: 99%
“…DIR gene family members are widely distributed in various plant species. Advances in genome sequencing technology have facilitated the identification of DIR genes in several plant genomes, including Arabidopsis [ 3 ], Capsicum annuum [ 15 ], Solanum lycopersicum [ 1 ], Solanum melongena [ 16 ], Oryza sativa [ 11 , 17 ], Hordeum vulgare [ 18 ] and Glycine max [ 14 ]. In this study, a total of 57 NtDIRs in tobacco and 33 StDIRs in potato were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inception of dirigent ( DIR ) genes dates back to 1985, when they were initially characterized in pea ( Pisum sativum ). But the function of DIR proteins were first identified in Forsythia intermedia in 1997, and then was later reported in Arabidopsis ( Arabidopsis thaliana ) ( Ralph et al, 2006 ; Cheng et al, 2018 ; Zhang et al, 2022 ; Luo et al, 2022 ). DIR belongs to a multi-gene family.…”
Section: Introductionmentioning
confidence: 99%